2022
DOI: 10.3390/cancers14174101
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Sequencing of Plasma-Derived vs. Urinary cfDNA from Patients with Triple-Negative Breast Cancer

Abstract: In breast cancer, the genetic profiling of circulating cell-free DNA (cfDNA) from blood plasma was shown to have good potential for clinical use. In contrast, only a few studies were performed investigating urinary cfDNA. In this pilot study, we analyzed plasma-derived and matching urinary cfDNA samples obtained from 15 presurgical triple-negative breast cancer patients. We used a targeted next-generation sequencing approach to identify and compare genetic alterations in both body fluids. The cfDNA concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Genomics-based analyses of urinary ctDNA have emphasized the somatic mutations linked to the primary tumors of BC patients, such as the PIK3CA and TP53 mutated genes, offering the non-invasive probing and real-time monitoring of BC relapse [ 164 ]. Based on cfDNA-seq, NF1 , CHEK2 , KMT2C, and PTEN were found to be the most frequently occurring mutated genes in the plasma and urine of BC patients [ 165 ].…”
Section: Breast Cancer Investigation In the Multi-omics Eramentioning
confidence: 99%
“…Genomics-based analyses of urinary ctDNA have emphasized the somatic mutations linked to the primary tumors of BC patients, such as the PIK3CA and TP53 mutated genes, offering the non-invasive probing and real-time monitoring of BC relapse [ 164 ]. Based on cfDNA-seq, NF1 , CHEK2 , KMT2C, and PTEN were found to be the most frequently occurring mutated genes in the plasma and urine of BC patients [ 165 ].…”
Section: Breast Cancer Investigation In the Multi-omics Eramentioning
confidence: 99%
“…Herzong et al suggested urine as an alternative liquid biopsy fluid from which to extract ctDNAs for TNBC clinical analysis. They compared the performances of ctDNA collection and characterization in both urine and plasma samples from 15 presurgical TNBC patients [ 57 ]. The analysis was performed by amplification of a coding region of 93 genes, known to be related to breast cancer, and their sequencing by Illumina NGS (NextSeqv2.5High Output 300 bp cassette).…”
Section: Liquid Biopsy and Circulating Cell-free Nucleic Acids In Tnbcmentioning
confidence: 99%
“…Bioinformatical analysis has revealed 431 somatic breast cancer-related variants shared in both fluids. Among these, the most common pathogenic and probable pathogenic mutations are NF1, CHEK2, KMT2C, and PTEN, which are tumor suppressor genes commonly implicated in TNBC onset and progression [ 43 , 44 , 45 , 46 , 47 , 48 , 57 ]. These results proved that both plasma and urine-derived ctDNA from TNBC patients could be efficiently analyzed using a targeted sequencing approach.…”
Section: Liquid Biopsy and Circulating Cell-free Nucleic Acids In Tnbcmentioning
confidence: 99%
“…CtDNA only represents a small part (0.1-10%) of the total cfDNA [10]. Still, cfDNA levels of cancer patients were reported to be increased compared to healthy individuals [11]. Increased cfDNA concentrations are not only cancer-specific but can also appear in other diseases or during pregnancy, physical exercise and physiological stress; thus, measuring the concentration alone is not sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…In urine, the half-life time of cfDNA is shorter than in plasma due to high levels of nucleases like DNase I and DNase II, as well as contaminants present in urine [9,10]. In previous studies, we were able to show that targeted sequencing of ucfDNA from patients with breast cancer was feasible without using stabilizing buffers when samples were processed within 2-4 h after collection [11,21]. However, the cfDNA yield from 10 mL of urine appeared to be low.…”
Section: Introductionmentioning
confidence: 99%